Pengembangan Media Pembelajaran Berbasis Genially pada Pembelajaran Pendidikan Pancasila Materi Gotong Royong di Lingkungan Sekitar Kelas V Sekolah Dasar - Tania, Valen; Masniladevi, Masniladevi (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited use of information technology by teachers in creating instructional media that are creative, engaging, enjoyable, and aligned with contemporary developments. The aim of this research is to develop Genially-based learning media for the Pancasila Education subject, specifically on the topic of gotong royong in the local environment, for fifth-grade elementary school students, which meets the criteria of validity, practicality, and effectiveness. The research employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Validation results indicate that the developed learning media achieved a very high level of validity: 95% in the material aspect, 94.2% in language, and 97.5% in media. Practicality tests also showed very high percentages from both teachers and students: 93.3% and 94.9% in the trial school, 95.5% and 95.8% in the first research school, and 97.7% and 94.3% in the second research school. Effectiveness tests measured through N-Gain scores yielded results of 76.38 at SDN 10 ATTS, 76.20 at SDN 10 Sapiran, and 76.01 at SDN 05 Tarok Dipo, all categorized as effective. Based on these findings, it can be concluded that the Genially-based learning media for Pancasila Education on the topic of gotong royong in the local environment for fifth-grade elementary students is suitable for use, having proven to be valid, practical, and effective in supporting the learning process.